Escitalopram-induced sinus bradycardia in coronary heart disease combined with depression: a case report and review of literature - Li, Liu-Cheng; Sun, Wen; Lv, Xiao-Qin; Xu, Yao-Yao; Hu, Ying; Shi, Jia-Na (Frontiers in Cardiovascular Medicine, 2024)
Patients with cardiovascular disease using antidepressant escitalopram may lead to unexpected adverse events. Here a rarely repeated sinus bradycardia due to escitalopram was first reported. An 82-year-old female with cardiac dysfunction using digoxin was demonstrated tachycardia (average heart rate of 93 times/min) by electrocardiogram (ECG). Then she began to take escitalopram and lorazepam due to depression, but sinus bradycardia (93.7% heart rate was < 60 times/min) and sinus arrest were first detected after three months, while its proportion decreased to 0.1% after escitalopram and digoxin discontinue for 1 day and the rhythm turned to normal two weeks later. After two months, escitalopram was prescribed again in combination with quetiapine, then 17.1% heart rate was sinus bradycardia. After escitalopram and quetiapine withdrawal, the ECG showed the heart rhythm was normalized again. No other drug changes were made during these periods. Escitalopram was deemed to be a highly possible cause of sinus bradycardia with Naranjo's Algorithm score. Besides, a literature review of escitalopram-mediated cardiovascular adverse events were analyzed. Empirically escitalopram should be discontinued immediately if iatrogenic causes cannot be ruled out. Besides, ECG monitoring in escitalopram-related cardiovascular adverse events was highlighted, especially in patients receiving particular drug classes simultaneously (i.e, sinoatrial node inhibitors, antipsychotics).